Polymer-Based Novel Lung Targeted Delivery Systems - Elmowafy, Enas; Osman, Rihab; A.H. Ishak, Rania (Current Pharmaceutical Design, 2017)
Background: Due to its unique features, the respiratory tract had received great attention as a promising non-invasive route for drug administration to achieve both local and systemic effects. Efforts spent to tailor systems able to overcome the lung defence mechanisms and biological barriers are followed in this review. Aerodynamic diameter, morphology, lung deposition and drug release profiles are the main criteria describing the selected new smart lung targeted delivery systems. Methods: Novel systems such as nanoparticles, nano-embedded-in microparticles (NEM), small microparticles (MP), large porous particles (LPP), PulmospheresTM and polymeric micelles are used to passively target different areas in the respiratory tract. The most common preparation methods are outlined in the article. Special emphasis was given to the characteristics of the polymers used to fabricate the developed systems. Efforts made to prepare systems using chitosan (CS), alginate (alg), hyaluronic acid (HA), gelatin and albumin as examples of natural polymers and poly lactic-co-glycolic acid (PLGA) and poly(#144;-caprolactone) (PCL) as synthetic polymers were compiled. Conclusion: The continuous development and work in the area of lung targeting resulted in the development of engineered smart platforms with the capability to carry small drug molecules, proteins and genes to treat a variety of local and systemic diseases.
Keywords: PLGA